ASSESSMENT STRATEGIES IN INTEGRATED FOREIGN LANGUAGE COURSES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Assessment in integrated foreign language courses plays a central role in ensuring students’ linguistic, cognitive, and intercultural development. Traditional assessment methods—primarily tests and written examinations—often fail to measure authentic communication skills and intercultural competence. Modern language education increasingly emphasizes competence-based, student-centered, and task-oriented assessment approaches that align with communicative and interdisciplinary learning goals. This paper examines a range of assessment strategies including formative, summative, authentic, performance-based, technology-enhanced, self- and peer-assessment methods within integrated foreign language instruction. Real classroom applications, rubrics, and comparative analysis of assessment types are provided to illustrate practical implementation. The study concludes that assessment in integrated courses should prioritize real-life tasks, intercultural understanding, creativity, and learner autonomy, thereby supporting holistic development and preparing learners for global communication.